Web-Based Clothes Sales Information System - Manalu, Dana Rio Efendi; Putri, Nency Extise; Putri, Yessy Prima (Journal of Applied Business and Technology, 2024)
Aliyelsha Damar Bordir is a business in the field fashion which is located on Jln. Rasuna Said No.38 Kurai Taji, South Pariaman, Pasir, Kec. Central Pariaman, Pariaman City. Aliyelsha Damar Bordir sells robes, koko clothes, kebaya clothes and mukenas. Clothing sales at the Aliyelsha Damar Bordir shop do not yet use information technology media so there are limitations in selling and marketing clothes at the Aliyelsha Damar Bordir shop not using information technology so it is difficult to do marketing. Based on the existing problems, the author designed a web-based information system for selling clothes at the Aliyelsha Damar Bordir shop. This research method uses the System Development Life Cycle (SDLC) with the Waterfall model. The programming languages used in building the system are PHP and MySQL. The aim of this research is to build a sales information system for the Aliyelsha Damar Bordir shop in selling clothing, implementing a clothing sales information system in improving clothing marketing and strengthening business value in the field of fashion and the results of this research are that the system built can make it easier for Aliyelsha Damar Bordir in the sales that will be built, as well as making it easier to provide information regarding goods and customer data.